The p110α and p110β Isoforms of Class I Phosphatidylinositol 3-Kinase Are Involved in Toll-Like Receptor 5 Signaling in Epithelial Cells - Sabine M. Ivison; Mohammed A. S. Khan; Nicholas R. Graham; Leila A. Shobab; Yu Yao; Arnawaz Kifayet; Laura M. Sly; Theodore S. Steiner (Mediators of Inflammation)
Background. Bacterial flagellin triggers inflammation in mammalian cells via Toll-like receptor (TLR) 5. Release of the chemokine IL-8 in response to flagellin involves NF-κB, p38 MAP kinase, and phosphatidylinositol 3-kinase (PI3K). However, PI3K has been reported to be either pro- or anti-inflammatory in different model systems. We hypothesized that this could be due to different activities of the p110α and β isoforms of PI3K. Results. PI3K and Akt were rapidly activated in Caco-2 colon carcinoma cells by flagellin. Using a plasmid-based shRNA delivery system and novel p110 isoform-specific inhibitors, we found that flagellin-induced IL-8 production was dependent on both p110α and p110β. However in the mouse, inhibition of p110β but not p110α reduced the increase of serum IL-6 levels induced by intraperitoneal injection of flagellin. Conclusions. These data demonstrate that the p110α and β isoforms of class IA PI3K are both required for the proinflammatory response to flagellin.